The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21037/jtd.2016.07.09
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes and lymph node assessment after induction therapy in patients with clinical N1 or N2 non-small cell lung cancer

Abstract: Induction CTx ± RT for cN1 or cN2 NSCLC patients did not affect EBL, operative times, or in-house mortality after RAVTS lobectomy. Patients undergoing RAVTS lobectomy after ICTx+ RT may be at greater risk for RLN injury, tracheal/bronchial injury, and pulmonary embolism. Fewer N2 LN stations, but not numbers of LNs, are assessed after ICTx ± RT. Induction therapy does not lead to increased downstaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…In spite of lacking multicenter prospective researches, a large number of retrospective studies proved that neoadjuvant chemotherapy did not add any extra risk to the occurrence of perioperative complications and mortality [7, 26, 27] even though mediastinal structures become differently affected after neoadjuvant chemotherapy. In addition, the optimal interval time from the end of neoadjuvant chemotherapy to surgery was proven to be not more than 6 weeks [28].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of lacking multicenter prospective researches, a large number of retrospective studies proved that neoadjuvant chemotherapy did not add any extra risk to the occurrence of perioperative complications and mortality [7, 26, 27] even though mediastinal structures become differently affected after neoadjuvant chemotherapy. In addition, the optimal interval time from the end of neoadjuvant chemotherapy to surgery was proven to be not more than 6 weeks [28].…”
Section: Discussionmentioning
confidence: 99%
“…There was substantial variability in operative time, and our mean duration of 227 minutes for lobectomy is on par with the majority of postinduction cases in the literature. For instance, Glover et al report an operative time for lobectomy of 264 minutes in patients who have undergone chemotherapy and 257 minutes in patients who have undergone chemoradiation, compared with 203 minutes in patients who did not receive induction treatment (18). In the current study, conversion to thoracotomy was required in 1 of the 5 anatomic resections attempted via a minimally invasive approach (20%).…”
Section: Commentmentioning
confidence: 99%
“…These results imply that the risk of PE in lung cancer patients receiving nonsurgical therapy is higher than those only undergoing lung resection. Furthermore, the overall frequency of PE in patients undergoing video-assisted thoracoscopic surgery (VATS) or robotic-assisted video thoracoscopic surgery (RAVTS) for lung cancer is 0.5% varying between 0 and 2% 26 , 27 , 29 , 34 , 37 , 45 , implying VATS or RAVTS is feasible in lung cancer.…”
Section: Incidence Of Pe In Lung Cancer Patientsmentioning
confidence: 99%
“…The majority of patients were male (15,754, 61.4%) and the mean age was 62.5 years, ranging from 19 to 93 11 , 13 - 24 , 26 , 28 , 29 , 31 - 41 , 43 - 45 , 47 - 51 . We also found that major patients only receiving surgery for lung cancer had stage I/II but those receiving nonsurgical conditions had stage III/IV according to table 2 , which might be one of causes of higher rate of PE in lung cancer patients with nonsurgical therapy.…”
Section: Incidence Of Pe In Lung Cancer Patientsmentioning
confidence: 99%